Keanekaragaman dan Potensi Lobster (Malacostraca: Palinuridae) di Pantai Pameungpeuk, Garut Selatan, Jawa Barat - Rianta Pratiwi (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Coral shrimp (Panulirus spp.) or known as lobster is a potential fishery commodity and economic value. The demand for domestic and export market continues to increase both as local consumption and export. Indonesia is the largest lobster fishery producer in almost all Indonesian waters, from the west coast of Sumatra to the east coast Jayapura, one of which is Pameungpeuk beach, South Garut, West Java. As a result of increasing demand, fishermen try to catch as many lobsters and the impact of lobster prices also in creases and whereas fishermen continuously take it from nature. This study was conducted to determine the diversity and potential of lobster species especially living in high wavy waters along the southern coast of Garut (Pamengpeuk), West Java.The results of observation are only three types of crayfish, namely: a. Panulirus homarus (green lobster sand); b. Panulirus longipes (lobster flower/ red lobster) and Panulirus versicolor (green lobster/bamboo); is most commonly found in the area of south Garut, Pameungpeuk beach with high and strong waves. The percentage of female P longipes species (42.88%) was higher compared to male P. homarus (40%) and ovigerous female of P. versicolor (37.14%). While the sexual ratio between P. homarus (1:2.0:2.0); P. longipes (1:1.2:1.0) and P. versicolor: 1:1.2:1.2 which statistically showed significantly different p <0.05.